Asymmetries in sub-extraction out of NP in Slovenian - Stepanov, Arthur (Linguistica (Ljubljana), 2016)
In this work, we aim to clarify the empirical paradigm that bears on two aspects of syntactic locality in Slovenian. First, building on previous work, we investigate how robustly Slovenian observes the syntactic locality constraint precluding constituent sub-extraction out of subject noun phrases. Second, we ask whether Slovenian allows Left Branch Extraction in interrogative and non-interrogative sentences. To elucidate both issues, we conducted a magnitude estimation study, the results of which support our previous claim that there is a subject island effect in Slovenian. Furthermore, our results suggest that Slovenian disallows Left Branch Extraction, in contrast with some other Slavic languages. We also discuss theoretical consequences of our empirical findings.
Keywords: îles syntaxiques; méthode d'estimation de grandeur; pridevnik; samostalniške zveze; skladenjski otoki; skladnja; Slovene; slovenščina; syntax; syntaxe; syntaxe expérimentale